International Relations: A Very Short Introduction - Wilkinson, Pau (New York Oxford University Press, 2007)
What is innovation? How can it be used? Why is failure so common in the process of innovation? This Very Short Introduction looks at what innovation is, what it has done for us, and why it has been so important in the last 150 years
Includes Index and Illustrations.
Keywords: International relations